Matching strategies for multi-antenna arrays in single and multiuser scenarios - Vasconcelos, Thiago Azevedo de (2020)
In modern mobile communication systems, arrays of many antennas, spaced in centimeters or millimeters, are sought to reach ambitious goals. However, the electromagnetic interactions between closely spaced antennas in the same array are usually not taken into consideration in the literature, leading to physically inconsistent communications systems models. In this scenario, this thesis presents the theory and the research behind the computation of the ergodic rates and capacities of multi-antenna communication systems accounting for the mutual coupling between the antenna elements. For this end, the Multiport Communication Theory was used as the theoretical framework to model the communication systems with circuit theoretic multiports, which encapsulate the effects of mutual coupling. Considering this effect, two systems were modelled: one conceived employing optimal decoupling and matching strategies through the use of specialized networks connecting high-power amplifiers and low-noise amplifiers to their respective antenna arrays, and the other conceived with no decoupling and a sub-optimal matching strategy using a direct connection between amplifiers and the antennas. Although capable of providing information theoretic level of performance to the system with them, decoupling and matching networks have major disadvantages related to the quantity of elements, all reactive, composing them. The elements can cause big Ohmic losses and frequency band limitations for large numbers of them. For the analysis of these networks, the systems’ rates and capacities are investigated in narrow and wideband cases. In the former, the networks and the antenna elements are considered to operate at their design frequency and, as such, the potential of these networks can be highlighted compared to the system without them. In the latter, the networks and the antenna elements operate in a frequency different from their design frequency, highlighting the effects of frequency variation in their performance and in the mutual coupling. Following these simulation cases, the total ergodic rates inside different bands of frequency are computed for one exemplary system to introduce the concept of optimal and critical bands, figures of merit that can help to determine whether or not the capacity gain brought by decoupling and matching networks is worth their complexity and everything it entails in terms of limitations (parasitics). Ultimately, one of the main goals of this thesis is to invoke on the importance of taking the mutual coupling between closely spaced antennas into account.